Investigation of Beta lactoglobulin gene variation in South African Holstein Friesian cows and its association with milk production traits - Makamu, Thlarihani Cynthia (My University, 2024)
It is important to predict the change in one trait in response to selection for another, hence, the knowledge of the connection between traits is essential for the improvement of milk components and yield of dairy animals. Moreover, the genes also must be taken into consideration when selecting animals due to their potential in affecting milk production traits. The Beta-lactoglobulin gene (β-LG) was detected on bovine chromosome 11 and encodes the main whey protein. The genetic effect of β-LG gene on milk production traits and quality of milk in South African Holstein Friesian cows is poorly understood. This study was conducted to identify the genetic markers of β-LG gene that might be utilised as selection criterion during breeding to improve milk production traits of Holstein Friesian cows. A total of one hundred (n = 100) South African Holstein Friesian cows aged 2 to 3 years from the Limpopo dairy farm were used in this study. Pearson’s correlation, student t-test analysis and DNA sequences were used for analysis. Milk samples (10 ml) were collected during morning milking using a measuring cup to represent the whole milking of each animal for detecting the milk constitution such as fat percentage (FP), protein percentage (PP), solid-not-fat (SNF), and lactose percentage (LP) using ultrasonic portable milk analyser (milko tester model- master mini). The data such as milk yield per day (MYD) and milk yield per 30 days (MY30D) were used for each used cow. Blood samples (5 ml) were collected from each animal underneath the tail using a butterfly needle and sent to Inqaba Biotechnology company for DNA extraction, amplification, and sequencing. The correlation results showed that MYD had a highly negative significant correlation (p ˂ 0.01) with PP and SNF. The correlation findings also indicated that MY30D had a highly negative statistical correlation (p ˂ 0.01) with FP and PP but was highly positive and significantly correlated (p ˂ 0.01) with SNF. DNA sequencing findings indicated the presence of 5 different SNPs. Two of the SNPs were non-synonymous (T/C) and (C/T) at positions 5174 and 5251 of exon 4 of the β-LG gene which were named 5174T>C and 5251C>T, respectively. The other 3 SNPs were found in intron 3 (C/G), (G/A), and (T/C) at positions 5123, 4982, and 5099 and named 5123C>G, 4982G>A, and 5099T>C, respectively. Chi-square results demonstrated that the population used was under Hardy-Weinberg equilibrium (HWE) for SNP 5123C>G and had a dominant allele C. Dominant alleles for SNPs 5174T>C, 4982G>A, 5099T>C, and 5251C>T were T, G, T, and C, respectively. Marker-trait association results revealed that genotypes of SNPs 5174T>C, 5099T>C, and 4982G>A had no association with v MY30D, PP, and SNF, however, it had a significant association with MYD, LP, and FP. In addition, a significant association between SNP 5123C>G and LP, FP, MY30D, and SNF, but it showed no association with MYD and PP. SNP 5251C>T displayed no association between its genotypes and milk yield and PP, however, it showed an association with FP, SNF, and LP. In conclusion, correlation results suggest that protein and solid-not-fat might be used to improve milk yield of Holstein Friesian cows. DNA sequencing results suggest that 5123C>G, 4982G>A, 5174T>C, 5099T>C, and 5251C>T were the SNPs found in β-LG gene of South African Holstein Friesian cows used in this study. Marker-trait association results suggest that TT genotype for SNPs 5174T>C, and 5099T>C of β-LG gene might be used as a genetic marker when improving milk yield per day and lactose %, whereas genotype CT might be used to improve fat %. Genotype CC of SNP 5123C>G might be used to increase milk yield per 30 days and solid-not-fat, while CG be used to improve lactose % and fat %. The TC genotype for SNP 5251C>T might be used as a genetic marker to increase solid-not-fat and lactose %, whereas CC genotype can be used to improve fat %. The GG genotype for SNP 4982G>A of β-LG gene might be used as genetic marker when improving milk yield per day and lactose %, whereas AG genotype might be used to improve fat %. Further studies need to be conducted on the β-LG gene single nucleotide polymorphisms and their association with milk production traits with a large number of animals and more milk production traits of South African Holstein Friesian cows.
Thesis (M. Sc. Agriculture (Animal Production)) -- University of Limpopo, 2024
Keywords: Milk yield; Single nucleotide polymorphisms; Protein; Fat; Lactose; Solid-not-fat; Lactoglobulins; Milk yield; Holsteins